Descriptive Values for Dancers on Baseline Concussion Tools - McIntyre, Lauren (J Athl Train, 2017)
CONTEXT: : Capturing baseline data before a concussion can be a valuable tool in individualized care. However, not all athletes, including dancers, have access to baseline testing. When baseline examinations were not performed, clinicians consult normative values. Dancers are unique athletes; therefore, describing values specific to dancers may assist those working with these athletes in making more informed decisions. OBJECTIVE: : To describe values for key concussion measures of dancers. Our secondary aim was to examine whether differences existed between sexes and professional status. Finally, we explored factors that may affect dancers' scores. DESIGN: : Cross-sectional study. SETTING: : Professional dance companies and a collegiate dance conservatory. PATIENTS OR OTHER PARTICIPANTS: : A total of 238 dancers (university = 153, professional = 85; women = 171; men = 67; age = 21.1 ± 4.8 years). MAIN OUTCOME MEASURE(S): : We calculated the total symptom severity from the Sport Concussion Assessment Tool–3rd edition; the Standardized Assessment of Concussion score; the modified Balance Error Scoring System score; and the King-Devick score for each participant. Group differences were analyzed with Mann-Whitney or t tests, depending on the data distribution. We used bivariate correlations to explore the effects of other potential influencing factors. RESULTS: : Participants demonstrated the following baseline outcomes: symptom severity = 16.6 ± 12.8; Standardized Assessment of Concussion = 27.5 ± 1.8; modified Balance Error Scoring System = 3.2 ± 3.1 errors; and King-Devick = 41.5 ± 8.2 seconds. A Mann-Whitney test revealed differences in King-Devick scores between female (40.8 ± 8.0 seconds) and male (43.4 ± 8.4 seconds) dancers (P = .04). An independent-samples t test also demonstrated a difference in modified Balance Error Scoring System scores between female (2.95 ± 3.1 errors) and male (3.8 ± 3.1 errors) dancers (P = .02). Age, hours of sleep, height, and history of concussion, depression, or injury did not display moderate or strong associations with any of the outcome measures. CONCLUSIONS: : Dancers' symptom severity scores appeared to be higher than the values reported for other athletes. Additional studies are needed to establish normative values and develop a model for predicting baseline scores.